Research in the history of economic thought and methodology. Vol. 27, pt. 1 a research annual - Samuels, Warren J., 1933-; Biddle, Jeff; Emmett, Ross B. (Emerald, 2009)
This book contains refereed articles on: contrasting relational conceptions of the individual in recent economics; the development of Adam Smith's style of lecturing; a comparison of problems encountered in the historian's work as editor, based upon editing Harrod's papers and Haberler's Prosperity and Depression; reminisciences on the New Deal by Jacob Viner; and Don Lavoie's lectures on comparative economic systems. It reviews essays on books about Schumpeter, Keynes, Mincer, comparative economic history, and the Chicago School; as well as reviews of books dealing with the repeal of the Corn Laws, economic systems and economic growth, the Enlightenment and post-modernism, and virtue ethics and capitalism.
Keywords: Business & Economics -- Economic History.; Economic history.; Economics -- Study and teaching (Higher); Economics -- Methodology.; Economics -- Research.; elektronické knihy; electronic books